2014
DOI: 10.1021/je400491p
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of CO2 in, and Densities and Viscosities of, the Piperazine + 1-Ethyl-3-methyl-imidazolium Acetate + H2O System

Abstract: Densities and viscosities of hybrid absorbents piperazine (PZ) (1) + 1-ethyl-3-methyl-imidazolium acetate ([Emim][Ac]) (2) + H 2 O (3) were respectively measured with different mass compositions (w 1 /w 2 /w 3 = 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…The addition of piperazine (PZ) was shown to greatly enhance the solubility, and to reduce the viscosity of IL, 1-ethyl-3-methyl-imidazolium acetate ([Emim][Ac]) (Li et al, 2014e). High absorption capacity was observed in aqueous blended system of (4 M MDEA and 1 M guanidinium trifluoromethanesulfonate [gua] [OTf].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…The addition of piperazine (PZ) was shown to greatly enhance the solubility, and to reduce the viscosity of IL, 1-ethyl-3-methyl-imidazolium acetate ([Emim][Ac]) (Li et al, 2014e). High absorption capacity was observed in aqueous blended system of (4 M MDEA and 1 M guanidinium trifluoromethanesulfonate [gua] [OTf].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…CO 2 solubilities in PPGME340, PC, and their mixtures were measured with the isothermal synthesis method similar to our previous works. , The widely used method , allows us to obtain the CO 2 solubilities without any sampling process by referring to the known amount of CO 2 and absorbent added into the absorption vessel and the pressure and temperature determinations at the isothermal condition.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure , the apparatus with the abovementioned method contains a gas storage vessel, an absorption vessel, a thermostatic system, a pressure detective system, and a vacuum system. The volumes of the two vessels were calibrated as shown in our previous work . First, the air in the two vessels was removed by the vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the use of hybrid solvents, containing amine solutions and physical solvents, may improve the efficiency of the current amine absorption processes. Hybrid solvents couple the properties of solvents to take advantage of favorable aspects of solvents while minimizing the disadvantages. , In recent years, ionic liquids (ILs), which are nonvolatile and recyclable solvents, ,, have been investigated as blends with amines and other physical solvents for carbon dioxide capture. ,, Lei et al showed that addition of omim­[TF 2 N] to methanol at a temperature of 313.2 K and pressures between 2 and 6 MPa increases the CO 2 solubility in comparison to pure methanol . Bernard et al indicated that the addition of bmim­[BF 4 ] to the aqueous monoethanolamine (MEA) solution reduces the corrosion of process equipment, which is one of the main disadvantages of the amine process .…”
Section: Introductionmentioning
confidence: 99%
“…Bernard et al indicated that the addition of bmim­[BF 4 ] to the aqueous monoethanolamine (MEA) solution reduces the corrosion of process equipment, which is one of the main disadvantages of the amine process . Furthermore, addition of an IL may help reduce the energy consumption for regeneration of amine solutions, , , while also increasing the absorption rate. ,, Haghtalab and Shojaeian showed that the enthalpy of solution of CO 2 in the MDEA + bmim­[acetate] solution is about half of the enthalpy of solution of CO 2 in the aqueous MDEA. It was concluded that replacing the aqueous media of the amine solution by the IL reduces the energy required for the solvent regeneration .…”
Section: Introductionmentioning
confidence: 99%